Shh expression in a rudimentary tooth offers new insights into development of the mouse incisor - Hovorakova, Maria; Prochazka, Jan; Lesot, Herve; Smrckova, Lucie; Churava, Svatava; Boran, Tomas; Kozmik, Zbynek; Klein, Ophir; Peterkova, Renata; Peterka, Miroslav (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2011)
For teeth as for any organ, knowledge of normal development is essential for the proper interpretation of developmental anomalies in mutant mice. It is generally accepted that tooth formation is initiated with a single signaling center that, in the incisor region, is exclusively related to the development of the functional adult incisor. Here, using a unique combination of computer-aided three-dimensional reconstructions and whole mount in situ hybridization of mandibles from finely staged wild-type mouse embryos, we demonstrate that several Sonic hedgehog (Shh) expression domains sequentially appear in the lower incisor region during early development. In contrast to the single Shh expression domain that is widely assumed to be present in each lower incisor area at ED12.5-13.5, we identified two spatially distinct regions of Shh expression that appear in an anterior-posterior sequence during this period. The initial anterior, more superficially located Shh expression region represented the rudimentary (so-called deciduous) incisor, whereas only the later posterior deeper situated region corresponded to the prospective functional incisor. In the more advanced embryos, only this posterior Shh expression in the incisor bud was detectable as a precursor of the enamel knot. This study offers a new interpretation of published molecular data on the mouse incisor from initiation through ED13.5. We suggest that, as with Shh expression, other molecular data that have been ascribed to the progressive development of the mouse functional incisor at early stages, in fact, correspond to a rudimentary incisor whose development is aborted.
Keywords: Hedgehog Proteins; Epithelium; epitel; Incisor; vývojová regulace genové exprese; Embryonic Development; Gene Expression Regulation, Developmental; čelisti; řezáky; trans-aktivátory; Animals; proteiny hedgehog; myši transgenní; zvířata; embryonální vývoj; myši; Trans-Activators; Jaw; Mice; Mice, Transgenic